(untitled) (Journal of Educational Management, 2000)
The study provides empirical evidence for the management of stress by teachers of secondary schools in Nigeria. A total of 3,466 teachers, drawn from secondary schools in Ogun State of Nigeria, returned their instrument for the study. Data were analysed using percentages and chi-square. The findings indicate that teachers frequently use the active behavioural and inactive (escape) strategies in managing stress. While the active congnitive strategies are never used, the teachers express mixed feelings about the adoption of the inactive behavioural strategies. Also, sex, qualifications and location have a relationship with the type of stress coping strategies adopted by the teachers.